2017
DOI: 10.4067/s0718-18762017000200002
|View full text |Cite
|
Sign up to set email alerts
|

Customer Behavior in Electronic Commerce: A Bayesian Approach

Abstract: Online shopping has increasingly replaced traditional retail shopping, as a large number of consumers have adopted it on a global scale. However, while it is well established in developed countries, e-commerce is still at an early stage in emerging markets, hence there is a need to unveil which factors contributes to its adoption. The main objective of this study is to integrate the theory of planned behavior, the theory of reasoned action, and the technology acceptance model using a Bayesian approach to deter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
31
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(36 citation statements)
references
References 68 publications
4
31
0
1
Order By: Relevance
“…Indonesian buyers are more driven by the low cost, fast delivery and availability of the product. With large number of increasing middle-class concentrated in big cities [1], [3], supported by high penetration of affordable smartphones [41], better services provided by application-based transportations [59], and government efforts to improve road and internet infrastructure [54], have spurred the rise of online buying behavior [12], [46]. Online buying trend has introduced new solutions to cater high costs economy in product delivery to end user [51].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indonesian buyers are more driven by the low cost, fast delivery and availability of the product. With large number of increasing middle-class concentrated in big cities [1], [3], supported by high penetration of affordable smartphones [41], better services provided by application-based transportations [59], and government efforts to improve road and internet infrastructure [54], have spurred the rise of online buying behavior [12], [46]. Online buying trend has introduced new solutions to cater high costs economy in product delivery to end user [51].…”
Section: Discussionmentioning
confidence: 99%
“…E-marketplaces provide huge market opportunities as well as the challenges [10] to survive with them. In order to survive, they are required to develop an appropriately sophisticated level of services [50] that might not be anticipated before, to serve their large buyers [12].…”
Section: Introductionmentioning
confidence: 99%
“…If we refer to the research conducted by Thamizhvanan and Xavier (2013), Kim and Ahn (2007), Chen and Barnes (2007), Sun (2010), Pavlou and Gefen (2004), Hsu et al (2014), Shadkam (2012), Becerra and Korgaonkar (2011), Kim JB (2012), and Schlaegel (2015) has a similar suggestion to put the this two construct to the model to complete the missing factor. Perceived behavioural control is also mentioned in several papers regarding digital platform such as Cheah et al (2015) and Dakduk et al (2017) which is interesting to be concluded into this study.…”
Section: Introductionmentioning
confidence: 86%
“…This is consistent with the research conducted by Giovanis et al (2012) , Safeena et al (2013) , Awa et al . 2015, Dakduk et al (2017) and Wei et al ( 217) found that perceptions of usefulness have a positive and significant effect on consumer intentions .…”
Section: The Influence Of Perceptions Of Usefulness On the Intention mentioning
confidence: 99%
“…In a study conducted by Yadav et al ( 2015) found that perceived ease of use did not have a positive and significant effect on consumer attitudes in the use of internet banking, this indicates that consumers feel that it is not easy to use internet banking and this result is contrary to the concept of the TAM itself which states that ease of use perceived influence positive attitude. Several other studies have found that perceived usefulness have a significant and significant effect on the intention to use (Hasio and Tang, 2013., Dakduk et al 2017) but several other studies get different results, where in a study conducted by Mutianah et al 2012, Yadav et al (2014) and Wei et al . (2017) found the opposite, namely the perceived usefulness did not have a significant effect on use.…”
Section: Introductionmentioning
confidence: 94%